2006
DOI: 10.1103/physreve.74.032901
|View full text |Cite
|
Sign up to set email alerts
|

Strong far-field coherent scattering of ultraviolet radiation by holococcolithophores

Abstract: By considering the structure of holococcoliths (calcite plates that cover holococcolithophores, a haploid phase of the coccolithophore life cycle) as a photonic structure, we apply a discrete dipolar approximation to study the light backscattering properties of these algae. We show that some holococcolith structures have the ability to scatter the ultraviolet (UV) radiation. This property may represent an advantage for holococcolithophores possessing it, by allowing them to live higher in the water column than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 15 publications
0
27
0
Order By: Relevance
“…Von Dassow et al (2009) showed for Emiliania huxleyi that transcript levels of genes whose products are involved in coccolithogenesis (Ca 2+ , H + and HCO 3 − transporters) are expressed much more in the diploid (heterococcolith) than in the haploid (holococcolith) phase which has non-calcified coccoliths. The few studies concerning environmental effects on holococcoliths (Quintero-Torres et al 2007, Fiorini et al 2011a, Pedrotti et al 2012 will be discussed in the relevant sections.…”
Section: Heterococcoliths and Holococcolithsmentioning
confidence: 99%
See 1 more Smart Citation
“…Von Dassow et al (2009) showed for Emiliania huxleyi that transcript levels of genes whose products are involved in coccolithogenesis (Ca 2+ , H + and HCO 3 − transporters) are expressed much more in the diploid (heterococcolith) than in the haploid (holococcolith) phase which has non-calcified coccoliths. The few studies concerning environmental effects on holococcoliths (Quintero-Torres et al 2007, Fiorini et al 2011a, Pedrotti et al 2012 will be discussed in the relevant sections.…”
Section: Heterococcoliths and Holococcolithsmentioning
confidence: 99%
“…Holococcoliths have been much less studied; an exception is Quintero Torres et al (2007), who modelled the probable scattering of radiation by their structure. They found that this would cause greater scattering of radiation in the 200 to 300 and 700 to 900 nm ranges.…”
Section: Influence Of Ultraviolet Radiation On Calcificationmentioning
confidence: 99%
“…These characteristics could have paleoceanographic implications and consequences in relation to ocean warming and the increasing acidification of the world oceans (Gibbs et al 2016). Estrada's interest in this phytoplankton group helped to show that some holococcolith structures (not present in all holococcoliths) can have the ability to scatter ultraviolet radiation (Quintero-Torres et al 2006), suggesting a possible strategy of increasing the reflection of UV light away from the cell, thus enhancing the ability of the organism to live higher in the water column. The studies in Mediterranean waters led to the description of a new coccolithophore, Picarola margalefii, dedicated to Ramon Margalef (Cros and Estrada 2004), which is now the symbol of the Margalef Award for Ecology (Fig.…”
Section: Insight Into the Taxonomy And Life Cycle Of Coccolithophoresmentioning
confidence: 99%
“…UVR can decrease phytoplankton productivity through direct damage to proteins and DNA or indirectly through stimulation of oxidative stress . Several studies , using different degrees of calcification of coccolithophores obtained by a variety of methods, have suggested that coccoliths may play a protective role to keep cells from being damaged by high levels of UVR. Xu et al .…”
Section: Introductionmentioning
confidence: 99%
“…UVR can decrease phytoplankton productivity through direct damage to proteins and DNA (8) or indirectly through stimulation of oxidative stress (9). Several studies (10)(11)(12)(13), using different degrees of calcification of coccolithophores obtained by a variety of methods, have suggested that coccoliths may play a protective role to keep cells from being damaged by high levels of UVR. Xu et al obtained different levels of calcification by adjusting the Ca 2+ concentration (14), whereas Guan et al adjusted the dissolved inorganic carbon (DIC) concentration (15).…”
Section: Introductionmentioning
confidence: 99%